Between Rationalism and Romanticism: Blanckenburg's Versuch über den Roman and the Transformation of Rationalist Metaphysics. (31st July 2022) - Klemm, Stephen
Abstract : This essay examines Blanckenburg's theory of the novel in relation to Leibniz's metaphysics. It argues that Blanckenburg theorizes the novel as uniquely suited to respond to the problem in Leibniz's metaphysics of how to bridge the gap between the apparent contingency of first‐person experience and the promise that the world is actually a well‐ordered whole. Whereas Leibniz must appeal to the Principle of Sufficient Reason to bridge this gap, Blanckenburg suggests that the novel can aid philosophical cognition by doing what philosophical thought cannot: create a world depicting the development of a human life in its totality. However, freed from its ontological basis, Blanckenburg's theory provides an important starting point for early Romantic aesthetic theory. Following Blanckenburg, the novel becomes a privileged medium not for copying life, but for offering a model for it, thereby providing an important impulse in Romanticism's reversal of rationalist hierarchies of philosophy and aesthetics.